A Note on Changes in the Wage and Unemployment Structures in Spain: Evidence from the Luxembourg Income Study - Patrick A. Puhani (Luxembourg Income Study (LIS), 2002)
This note tests whether the extraordinary rise in Spanish unemployment in the 1980s can be traced back to rigidities in the wage structure in the face of relative net demand shocks against the unskilled (this claim is also known as the 'Krugman hypothesis'). I can establish that youth joblessness is key to the Spanish unemployment problem, but sampling procedures in the data set make it impossible to track the youth unemployment problem across time in a satisfactory way. Even though high youth unemployment is consistent with the Krugman hypothesis, substantial skill upgrading of the Spanish labor force in the1980s explains why the low education groups did not experience an increase in relative unemployment.
Keywords: 330; Arbeitslosigkeit; Jugendarbeitslosigkeit; Fachkräfte; Berufsbildung; Lohnstruktur; Spanien